AFQ056 in Parkinson patients with levodopa‐induced dyskinesia: 13‐week, randomized, dose‐finding study. Issue 13 (12th July 2013) - Stocchi, Fabrizio; Rascol, Olivier; Destee, Alain; Hattori, Nobutaka; Hauser, Robert A.; Lang, Anthony E.; Poewe, Werner; Stacy, Mark; Tolosa, Eduardo; Gao, Haitao; Nagel, Jennifer; Merschhemke, Martin; et al.
ABSTRACT: AFQ056 is a novel, selective metabotropic glutamate receptor 5 antagonist. This was a 13‐week, double‐blind, placebo‐controlled study. Patients with Parkinson's disease and moderate‐to‐severe levodopa (l ‐dopa)‐induced dyskinesia who were receiving stablel ‐dopa/anti‐parkinsonian treatment and were not currently receiving amantadine were randomized to receive either AFQ056 (at doses of 20, 50, 100, 150, or 200 mg daily) or placebo (1:1:1:1:2:3 ratio) for 12 weeks. The primary outcome was the modified Abnormal Involuntary Movements Scale. Secondary outcomes included the 26‐item Parkinson's Disease Dyskinesia Scale, the Patient's/Clinician's Global Impression of Change, and the Unified Parkinson's Disease Rating Scale parts III (motor evaluation) and IV (severity of motor complications). Safety was assessed. In total, 98 of 133 (73.7%) AFQ056‐treated patients and 47 of 64 (73.4%) patients in the placebo group completed the study. Baseline characteristics were comparable. Patients randomized to AFQ056 200 mg daily administered in 2 doses demonstrated significant improvements at Week 12 on the modified Abnormal Involuntary Movements Scale compared with placebo (difference, −2.8; 95% confidence interval [CI], −5.2, −0.4; P  = 0.007). Based on final actual doses, there was a dose‐response relationship on the modified Abnormal Involuntary Movements Scale, with 200 mg daily demonstrating the most robust effect (difference, −3.6; 95% CI, −7.0, −0.3; P  = 0.012). Improvements in dyskinesia were supported by change on Unified Parkinson's Disease Rating Scale part IV item 32 (50 mg daily: difference, −0.7; 95% CI, −1.1, −0.2; P  = 0.003; 200 mg daily: difference, −0.5; 95% CI, −0.8, −0.1; P  = 0.005). No significant changes were observed on the 26‐item Parkinson's Disease Dyskinesia Scale, the Unified Parkinson's Disease Rating Scale part IV item 33 or items 32 and 33, or the Patient's/Clinician's Global Impression of Change. Unified Parkinson's Disease Rating Scale part III scores were not significantly changed, indicating no worsening of motor symptoms. The most common adverse events (with incidence greater with AFQ056 than with placebo) were dizziness, hallucination, fatigue, nasopharyngitis, diarrhea, and insomnia. AFQ056 demonstrated anti‐dyskinetic efficacy in this population without worsening underlying motor symptoms. These results will guide dose selection for future clinical trials. © 2013 International Parkinson and Movement Disorder Society